Growth mindset of anxiety and avoidant coping as mediators of anxiety across the first year of college: A longitudinal survey of college students in the context of the COVID-19 pandemic - Erin Henshaw; Susan Kennedy; Andrea Lourie; Drexler James; Folly Folivi (Health Psychology Research)
# Introduction